On the Salt Bath Cleaning Operations for Removal of Lubricants on the Surface of Titanium Alloy Aerospace Fasteners - Richard Turner; Caitlin Edgerton; Jack Hobby; Jakub Mierzejewski; Taahir Patel; Nils Warnken (Lubricants)
Aerospace fasteners are a ubiquitous component within the aerospace, air-frame, and aero-engine industries due to the essential role they play in structural integrity. Ti-6Al-4V is a common material for fasteners to be manufactured from, owing to the excellent strength-to-density ratio the material possesses, allowing for weight-saving in an application where weight is penalised by loss of fuel efficiency. The manufacture of aerospace pins sees a solid-state lubricant applied over the surface of the bar stock, at the titanium manufacturers, which aids forging processing; however, this lubricant layer must be fully removed post-forging to allow for solution heat treatment operations to achieve the desired mechanical properties. Whilst the exact composition of the lubricant is proprietary to the titanium producers, this can make understanding the removal via salt bath processing difficult. As such, the lubricant has been analysed and characterised to understand the primary chemical composition of the lubricant. Furthermore, the salt bath process has been studied to understand the efficacy of the cleaning process and the impact that variation in the salt bath hold time has or that adding some method of agitation to the molten salt in the bath as it cleans the surface lubricant off the Ti-6Al-4V fastener has. The salt bath cleaning process can cause a bottleneck to the full manufacturing route for the aerospace fasteners. Results suggest that there is some margin to reduce the hold time, or that by adding in a dipping process to increase agitation, it can also allow for lower hold times.